2012
DOI: 10.1097/ccm.0b013e318251517a
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin usefulness for the initiation of antibiotic treatment in intensive care unit patients*

Abstract: Procalcitonin measuring for the initiation of antimicrobials did not appear to be helpful in a strategy aiming at decreasing the antibiotic consumption in intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 17 publications
0
90
2
Order By: Relevance
“…However, further evidence is needed to support this contention. In the previously mentioned study of ICU patients, 22 no advantage was seen with procalcitonin protocol use, while a systematic review of studies in ICU patients suggested some advantages to its use. 21 Available randomized trials of procalcitonin protocols in CAP patients lack comparisons with the use of other evidence-based guidelines.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, further evidence is needed to support this contention. In the previously mentioned study of ICU patients, 22 no advantage was seen with procalcitonin protocol use, while a systematic review of studies in ICU patients suggested some advantages to its use. 21 Available randomized trials of procalcitonin protocols in CAP patients lack comparisons with the use of other evidence-based guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…6,21 More recently, in a single-center randomized controlled trial of ICU patients in Belgium, antibiotic consumption was not reduced and test sensitivity and specificity were suboptimal in differentiating confirmed and probable infection from possible and no infection, with an ROC curve area of 0.69. 22 Similar studies, preferably multicenter and international, should be performed to examine procalcitonin protocol use in CAP patients. Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Layios et al (32) applied a PCT algorithm where antibiotics were discouraged if PCT <0.25 ng/mL and encouraged if PCT >1 ng/mL in 509 patients suspected of infection on admission or during ICU stay and found no difference in the rate of initiation of therapy, percentage of days on antibiotics or overall defined daily dose of antibiotics between PCT and control groups. Bouadma et al (33) in the PRORATA trial (n=630) used a similar algorithm and showed a reduction of antibiotic exposure in the PCT group (more days without antibiotics, 14.3±9.1 vs. 11.6±8.2 days in control group, 95% CI, P<0.0001) and a 7% absolute risk reduction for initiating antibiotics.…”
Section: Adult Icu Patientsmentioning
confidence: 99%
“…The growing pressure of multidrug-resistant bacteria in the ICU environment, combined with considerations regarding cost and limitation of drug toxicity and interactions [26,27], offered the perfect opportunity for a new appraisal of this biomarker, which had somehow failed to fulfill its promises. It is considered to be useful because of favorable kinetics [28] and a high negative predictive value [17,[29][30][31].…”
Section: Core Textmentioning
confidence: 99%